Comparison of common risk stratification indices to predict outcomes among stage IV cancer patients with bowel obstruction undergoing surgery. Issue 3 (16th October 2017) - Bateni, Sarah B.; Bold, Richard J.; Meyers, Frederick J.; Canter, Daniel J.; Canter, Robert J.
Abstract : Background and Objectives: Among patients with disseminated malignancy (DMa), bowel obstruction is common with high operative morbidity. Since preoperative risk stratification is critical, we sought to compare three standard risk indices, the American Society of Anesthesiology (ASA) classification, Charlson comorbidity index (CCI), and modified frailty index (mFI). Methods: We identified 1928 DMa patients with bowel obstruction who underwent an abdominal operation from 2007 to 2012 American College of Surgeons National Surgical Quality Improvement Program. Multivariate analyses assessed predictors of prolonged length of stay (LOS), 30‐day serious morbidity and mortality. Receiver operating characteristics' areas under the curves (AUCs) for risk indices scores and 30‐day mortality were assessed. Results: Serious morbidity and mortality rates were 20.4% and 14.8%. ASA and CCI did not predict serious morbidity or prolonged LOS, but were predictors of mortality. The mFI did not predict prolonged LOS, but did predict serious morbidity and mortality. Subgroup analyses showed similar results. There were no significant differences between ASA, CCI, and mFI AUCs for mortality. Conclusions: ASA, CCI, and mFI are limited in their ability to predict postoperative adverse events among DMa patients undergoing surgery for bowel obstruction. These data suggest that a more tailored preoperative risk stratification tool would improve treatment planning.